ANALISIS NILAI-NILAI KECAKAPAN ABAD 21 DALAM BUKU SISWA SD/MI KELAS V SUB TEMA 1 MANUSIA DAN LINGKUNGAN - Widodo, Arif; Indraswati, Dyah; Sobri, Muhammad (Tarbiyah : Jurnal Ilmiah Kependidikan, 2019)
This study aims to describe the 21st century skills values contained in the fifth grade student?s book sub theme 1 (Human and Environment). The method used is content analysis with data reduction stages, data exposure, and drawing conclusions. Data source in this study is buku lingkungan sahabat kita, the 2013 thematic integrated curriculum book for SD/MI grade V. The results of this study indicate that 21st century skills have been developed in learning activities, let?s discuss, let?s write, let?s observe, let?s try, let?s practice, let?s sing, let?s sing, let?s contemplate, and activities with parents.